A road to bring Brij52 back to attention: Shear stress sensitive Brij52 niosomal carriers for targeted drug delivery to obstructed blood vessels. (December 2018) - Arjmand, Shokouh; Pardakhty, Abbas; Forootanfar, Hamid; Khazaeli, Payam
Abstract: Thrombosis is a shared perpetrating event in the pathophysiology of several cardiovascular disorders such as ischemic stroke, venous thromboembolism, atherosclerosis, and myocardial infarction. Despite holding a wide range of ammunition in our arsenal to ameliorate such conditions, we are still facing with many stumbling blocks in the satisfactory pharmacotherapy of cardiovascular diseases among which the risk of hemorrhage and life threatening drug interactions can be highlighted. Our hypothesis focuses on mimicking the nature of platelet activation, to design a novel targeted delivery system based on the alterations of a physical parameter, the hemodynamic shear stress, to aim at the offending thrombi in an attempt to offer a noninvasive, rapid, and monitoring-free method that not only can prolong the circulation time of the cargo, but also deliver it locally and reduce both the undesirable adverse effects and drug interactions. Brij52 is our chosen candidate due to its unique non-spherical morphology after forming a niosomal vesicle. We surmised that thanks to its non-spherical shape, diverse shear rates may generate different shear stresses to its equators and axes which might result in the breakdown or at least distortion of niosomal structure under elevated shear stress. The vesicles have to be synthesized in the size of platelets or in the nano-sized scale. In order to prolong the time vesicles are circulating in the blood, PEGylation may help and to make such carriers highly selective to be only activated during pathophysiological clot formation, attachment of domain A1 von Willebrand factor can be of benefit to lead this proposed delivery system to the site of thrombus formation where shear rate exceeds those of 1000 s −1 . There is now an emerging fast growing universal research on shear activated carriers, and the present theory is an endeavor to reach a successful treatment strategy to combat cardiovascular diseases based on the hypothesis that a non-spherical nano-carrier such as Brij 52 niosomal vesicle can be of paramount benefit to deliver current antithrombotic agents in a targeted and controlled manner in the presence of elevated shear stress of the obstructed blood vessels. With more radical advanced drug delivery systems being developed and new strategies being pursued, there will be more options in our arsenal to represent a promising avenue for achieving preventive, well-tolerated, and intelligent drug carriers to circumvent the drawbacks of antithrombotic pharmacotherapy.